Cities and cultural diversity in Al-Ghuraba newspaper’s novel A Date at the Café by Ali Badr (Journal of the College of Basic Education, 2025)
This constant movement ensures that we recognize the cultural characteristics that these cit The novel Al-Ghuraba newspaper, by Ali Badr, is based on movement between cities that belong to different countries that do not share a specific culture, language, or customs. This continuous movement ensures that we learn about the cultural characteristics that these cities carry. ies carry, and strive to create a free environment for communication between different identities. “Ali Badr” sought In this novel, he seeks to break the space-time barrier. He presents us with events that violate his logical line, so he approaches the miraculous journey that does not recognize this restriction. He brings in historical and cultural figures to engage in literary discussions with them that express harmony between multiple races, cultures, and identities. The research seeks to reveal the cultural discourse that does not withstand all political, ideological and ethnic obstacles, and which is characterized by a multiplicity of voices and multiple ideologies.